"NRF2 addiction" in lung cancer cells and its impact on cancer therapy. (28th December 2019) - Hammad, Ahmed; Namani, Akhileshwar; Elshaer, Mohamed; Wang, Xiu Jun; Tang, Xiuwen
Abstract: Nuclear factor erythroid 2-like factor 2 (NRF2) is a master regulator of the antioxidant enzymes and the detoxification proteins that play major roles in redox homeostasis. Although it plays a protective role against tumorigenesis, emerging evidence has shown that the NRF2 pathway is frequently altered in different types of cancer, including lung cancer. NRF2 activation influences many of the hallmarks of cancer and their signaling pathways, mainly apoptosis, proliferation, angiogenesis, metastasis, and metabolic reprogramming to establish cellular metabolic processes leading to "NRF2 addiction" in lung cancer cells. Intriguingly, constitutive activation of NRF2 promotes cancer development as well as resistance to chemotherapy and radiotherapy, and these malignant phenotypes lead to a poor prognosis in lung cancer patients. Therefore, targeted inhibition of the NRF2 together with traditional chemotherapy, radiotherapy, and immunotherapy, may be a promising approach to improving the survival rates of the NRF2-addicted lung cancer cases. Here we summarize the recent advances in NRF2-addicted lung cancer. Highlights: Aberrant activation of NRF2 pathway in lung cancer. NRF2 activation influences many of the hallmarks of cancer. Therapeutic strategies for NRF2 addicted lung cancer.